TIKTOK SEBAGAI MEDIA PEMBELAJARAN DALAM MELATIH KETERAMPILAN BERBICARA DI DEPAN UMUM MAHASISWA BARU JURNALISTIK UIN JAKARTA - Bharadika - Arok; Muhammad Rizki A.R; Wahyunengsi Wahyunengsi (Jurnal Prodi Ilmu Komunikasi, 2023)
In the current era, social media is very tied to people's daily lives, this makes social media have great potential for various fields, especially in the field of education. Social media such as Tik Tok, Instagram, Twitter, Facebook have become a place for learning in addition to being a medium of interaction. In fact, Tik Tok is one of the apps with the most users. In this study, the author aims to explain the results of observations from the development of public speaking skills of UIN Syarif Hidayatullah Jakarta journalism students on the Tik Tok application. This research uses a qualitative approach with a questionnaire method. As a result, new journalism students of UIN Jakarta were helped by the Tik Tok application for their ability to speak in public. Although, the confidence to speak and appear in front of the camera is still low.